Efforts to increase teacher knowledge in implementing the merdeka curriculum in Cisauk District, Tangerang - Sri Hapsari Wijayanti; Yohanna Claudia Dhian; Alfonso Horrison; Margaretha Theresia; Theodora Jessica (Community Empowerment, 2023)
Teachers and school principals who are members of the teacher working group (KKG) cluster 10, Cisauk District, Tangerang Regency, feel unprepared to implement the merdeka curriculum in the 2023/2024 academic year. This is due to their lack of participation in training and guidance on the practice of implementing the merdeka curriculum. The aim of this community service is to enhance the knowledge and understanding of teachers in KKG cluster 10, Cisauk District, in implementing the merdeka curriculum. The program stages include preparation, training, monitoring, and evaluation. Based on the completeness of each question, teachers still need assistance in creating teaching modules, and individual teachers reported an increase in knowledge. However, overall, there was a 24-point increase in knowledge. This program will continue with assistance in creating teaching modules for implementing the merdeka curriculum.